THE USE OF FOLKTALES IN TEACHING LISTENING COMPREHENSION - Muhammad Asrul Sultan (Publikasi Pendidikan, 2015)
The objectives of this research are: (1) To find out whether or not the use of folktales in teaching listening comprehension is effective to improve the students’ listening comprehension ability and (2) To elaborate the students motivation toward the use of folktales in teaching listening comprehension is effective to improve the students’ listening comprehension ability.This research is a quasi experimental research and it employed a cluster random sampling technique. The researcher randomly select two class from six class of the tenth years students. Group A was as experimental group and group B became control group. The data were collected by using test and questionnaire. The data of the students’ learning outcomes on listening were collected by using listening test while the data on the students’ motivation were collected by using questionnaire. Those data were then analyzed descriptively and inferentially using SPSS 16.0 and Likert Scale.The result of data analysis indicated that: (1)the learning outcomes on listening of the tenth years students of SMA Negeri 1 Parepare taught by using folktales in teaching listening significantly increased after the treatment. “The use of folktales in teaching listening comprehension” effective in improving listening comprehension achievement of the students better than conventional activity as indicated by the t-test value 7.571 and the p-value (2-tailed) .000 which was not greater than .05 level of significance; (2) the students were motivated in learning listening by using folktales, as indicated by the mean score 83.83 from the questionnaire. It means that the students were classified strongly motivated students.Key words: folktales and listening comprehension